Fertility preservation: is there a model for gender-dysphoric youth? - Laidlaw, Michael K.; Lahl, Jennifer; Thompson, Angela (Frontiers in Endocrinology, 2025)
Assisted reproductive technologies (ART) and cryobiology advances over the past decades have offered hope to cancer patients who might not otherwise be able to have biological offspring due to the toxic nature of therapies that may lead to subfertility or infertility. Fertility preservation (FP) for youths with gender dysphoria (GD) poses an additional set of complications and obstacles because of the use of medications which block normal pubertal development such as gonadotropin-releasing hormone analogues (GnRHa) and medications which directly alter the genital tract such as cross sex hormones. Here we review the current state of knowledge and ethical concerns with FP focusing on issues when FP is used during adolescent and preadolescent reproductive development in the context of cancer and gender dysphoria treatment. Particularly for youths with GD, very little evidence-based research has been performed and much remains unknown with respect to long term harms to reproductive health and the ultimate success of FP and conception.